Efektivitas Layanan Bimbingan Kelompok Dengan Teknik Sosiodrama Dalam Meningkatkan Kemampuan Interaksi Sosial Anak: The Effectiveness Of Group Guidance Services With Sociodrama Techniques In Improving Children's Social Interaction Skills - Krisnandari, Elizabeth Selvia; Sapto Irawan; Adhi Krisna Maria Agustin (Scholaria: Jurnal Pendidikan dan Kebudayaan, 2024)
The purpose of this study is to examine the effectiveness of group guidance using sociodrama techniques to improving social interaction skills of children aged 12-14 years at PPA Andreas IO-0803 Salatiga. This research is an experimental research. The type of the research is a pseudo-experiment with the Nonequivalent Control Group Design method. The subjects of this study are 10 children who have social interaction skills in the low category. The data collection technique using social interaction. The data analysis technique used in this study is Mann Whitney test. The results scale social interaction experienced a significant increase as aren’t of the treatment using sociodrama techniques in group guidance. The results of data analysis obtained the number of Asymp. Sig (2-tailed) 0.009 is greater than 0.05, hence Ha is accepted. In conclusion, social interaction can be improved through group guidance with sociodrama techniques in PPA children aged 12-14 years at PPA Andreas Salatiga.